2021
DOI: 10.1101/2021.02.15.431229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the phenology of protists: Recurrent patterns reveal seasonal variation of protistan (Rhizaria: Cercozoa, Endomyxa) communities in tree canopies

Abstract: Tree canopies are colonized by billions of highly specialized microorganisms that are well adapted to the extreme microclimatic conditions, caused by diurnal fluctuations and seasonal changes. In this study we investigated seasonality patterns of protists in tree canopies of a temperate floodplain forest via high-throughput sequencing with group-specific primers for the phyla Cercozoa and Endomyxa. We observed consistent seasonality and identified divergent spring and autumn taxa. Tree crowns were characterize… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Habitats in the canopy, however, were dominated by the obligate biotrophic genera Peronospora and Hyaloperonospora (Figure 4). Tree canopies have only recently been subject to studies on microbial diversity (Jauss et al, 2020a(Jauss et al, , 2020bWalden et al, 2021;Herrmann et al, 2021), indicating tree canopies to be a hitherto neglected reservoir for parasitic microorganisms. Species of the genus Hyaloperonospora are known to be highly host-specific, infecting plant species of Brassicaceae and closely related families (Lee et al, 2017 and references therein).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Habitats in the canopy, however, were dominated by the obligate biotrophic genera Peronospora and Hyaloperonospora (Figure 4). Tree canopies have only recently been subject to studies on microbial diversity (Jauss et al, 2020a(Jauss et al, , 2020bWalden et al, 2021;Herrmann et al, 2021), indicating tree canopies to be a hitherto neglected reservoir for parasitic microorganisms. Species of the genus Hyaloperonospora are known to be highly host-specific, infecting plant species of Brassicaceae and closely related families (Lee et al, 2017 and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…A common pattern in microbial community ecology studies is a high seasonal variability (Nolte et al, 2010;Fiore-Donno et al, 2019;Fournier et al, 2020;Walden et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the former study only analysed one time point, while the latter study that included air samples could show a strong temporal variability in community composition. Accordingly, several studies have shown that seasonal variability can influence protistan communities, to some extent (Nolte et al, 2010;Fiore-Donno et al, 2019;Fournier et al, 2020;Walden et al, 2021). For cercozoan communities, Walden et al (2021) could show annually reoccurring succession patterns in the phyllosphere.…”
Section: Introductionmentioning
confidence: 99%